Seroprevalence of Leptospirosis in Suspected High-Risk Sudanese Patients; A Pilot Exploratory Study - Nada Abdelghani Abdelrahim; Wisal Mustafa Ibrahim Mohammed (Tropical Health and Medical Research, 2022)
The extent of leptospirosis is unknown in Sudan, and it might be mistaken for other more common febrile infectious diseases. Leptospirosis might also be associated with renal diseases that are common in Sudan. We intended to explore the existence of human leptospirosis in suspected high-risk patients in Khartoum, Sudan, via sero-screening random febrile patients and those undergoing renal dialysis. This pilot exploratory study was conducted over six months, from April to September 2013. Four hospitals were selected conveniently following a non-random sampling approach. One hundred nineteen febrile patients (with or without definitive diagnosis) and patients under renal dialysis were included, and their serum specimens and clinical and demographic data were collected. Sera were screened qualitatively for the existence of anti-leptospiral IgM antibodies using a rapid lateral flow immune-sorbent assay. Ethical clearance and official permissions were obtained. Of the 119 patients, 57 (47.9%) had end-stage renal disease. They were under dialysis at Renal Dialysis Unit in Asbab Charity Hospital in Bahri, 47 (39.5%) were febrile with unknown origin attending the Tropical Medicine Hospital in Omdurman, and 15 (12.6%) were febrile and were diagnosed as having malaria or typhoid and attended Yastabshiron Medical Centre and Bashauer Teaching Hospital. The prevalence of anti-leptospiral IgM antibodies among all 119 screened patients was 7%. The prevalence among the 57 with the end-stage renal disease was 9%, and among the 47 with a fever of unknown origin was 6%. The prevalence among the 15 with a fever of known origin (diagnosed as malaria or typhoid) was 0%. Almost all positive patients had recurring episodes of fever, were in close contact with livestock, were farmers, and had an untreated natural source for drinking water. Human leptospirosis does exist in this targeted population. It is probably a common febrile condition and can be easily considered one of the major causes of chronic kidney disease affecting people in Sudan. A national sero-screening for leptospirosis among those living in high-risk geographical areas and those at occupational risk is highly recommended.